MANAGEMENT OF SPORT COMPLEXES - Marian STAN (Economy and Sociology, 2015)
The actuality of the investigated theme. Nowadays, human evolution, including his intellectual development, proves the fact that especially the creation manpower and the employment was the solution of all life’s ambitions in society. So, the fact is that in reality, man is the most important capital of the society. Also, in an individual’s life, the practice of sport plays a significant role and that’s why the initiation, the launch and the management of sports complexes activity reveal the existence of specific management features that we will identify and explain in the current study. The aim of the research refers to the elaboration of a theoretical base of the management of the sport complexes, to the pointing of the factors that influence the efficient existence and function of a sport complex in our country and to the determination of the responsibilities that have a manager who directs successfully the activity of the sport complexes. The investigation is based on theoretical methods, such as: scientific documentation, analysis, synthesis, comparison and on empirical research methods, like: study of researched literature and observation. The results of the research indicate the fact that the profitability of a sport complex must assure a particular structure to avoid the bankruptcy risk and also, that the administration of the sport complexes activity must keep in view the reliable functions of the contemporaneous management.